The GoodHope Exercise and Rehabilitation (GEAR) Program for People With Ehlers-Danlos Syndromes and Generalized Hypermobility Spectrum Disorders - Mittal, Nimish; Santa Mina, Daniel; Buryk-Iggers, Stephanie; Lopez-Hernandez, Laura; Hussey, Laura; Franzese, Alyssa; Katz, Joel; Laflamme, Camille; McGillis, Laura; McLean, Lianne; Rachinsky, Maxim; Rozenberg, Dmitry; et al. (Frontiers in Rehabilitation Sciences, 2021)
Introduction The Ehlers Danlos Syndromes (EDS) and Generalized Hypermobility Spectrum Disorders (G-HSD) comprise a heterogeneous group of genetic disorders of abnormal synthesis and/or maturation of collagen and other matricellular proteins. EDS is commonly characterised by manifestations such as multi joint hypermobility that can lead to musculoskeletal pains, subluxations and dislocations, fragile skin, organ dysfunction, and chronic significant diffuse pain with fatigue, deconditioning eventuating to poor quality of life. Evidence suggests exercise and rehabilitation interventions may ameliorate symptoms of unstable joints, recurrent subluxations/dislocations, and chronic widespread musculoskeletal pain. To date, there have only been a few reports describing exercise and rehabilitation care strategies for people with EDS. Methods In this manuscript, we describe the GoodHope Exercise and Rehabilitation (GEAR) program, its overarching principles, as well as the program development and delivery model. The GEAR program aims to decrease functional impairment, reduce pain, increase confidence in symptom self-management, and provide a community of support for people with EDS/G-HSD. To achieve these goals, we detail the model of care that includes exercise and rehabilitation therapy, education for self-management, and support accessing relevant community resources. Strengths and Limitations of the Study GEAR represents a novel exercise and rehabilitation care model for people with G-HSD and various clinical EDS subtypes, beyond the commonly included hEDS subtype. Systematic collection of data via validated measurements is ongoing and will guide the refinement of GEAR and support the development of emerging exercise and rehabilitation programs for people with EDS.